1998
DOI: 10.1038/bjc.1998.672
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C-α isoform enhances the P-glycoprotein expression and the survival of LoVo human colon adenocarcinoma cells to doxorubicin exposure

Abstract: Summary The aim of the present paper was to analyse the effect of long-term inhibitory treatment, for at least 7 days, of individual protein kinase C (PKC) isoforms on the survival of LoVo human colon adenocarcinoma cells to doxorubicin exposure. The treatment for 2 h, after plating the cells, and after 3 days with 1 gM Go6976, a specific inhibitor of protein kinase C (PKC)-a and -i1 isoforms, induced on day 7 in LoVo cell lines (WT) a significant increased survival when these cells were exposed to increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…6B). These results are in agreement with previously published work (La Porta et al, 1998) that indicated PKCα plays a pivotal role in drug resistance and mediation of anti-apoptotic events in doxorubicin treated cells. Furthermore, inhibition of PKCα led to increased cleavage of PARP in both types of cells (Fig.…”
supporting
confidence: 83%
“…6B). These results are in agreement with previously published work (La Porta et al, 1998) that indicated PKCα plays a pivotal role in drug resistance and mediation of anti-apoptotic events in doxorubicin treated cells. Furthermore, inhibition of PKCα led to increased cleavage of PARP in both types of cells (Fig.…”
supporting
confidence: 83%
“…[30][31][32][33] However, some reports have indicated that PKC isoforms are located in the nucleus or are translocated to the nucleus. Similarly, other reports have suggested a direct relationship between nuclear PKC and tumorigenesis, [34][35][36][37] although the regulatory role of nuclear PKC in cancer is not completely understood. [34][35][36][37][38][39] In this study, we showed that HMGB1 interacted with PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other reports have suggested a direct relationship between nuclear PKC and tumorigenesis, [34][35][36][37] although the regulatory role of nuclear PKC in cancer is not completely understood. [34][35][36][37][38][39] In this study, we showed that HMGB1 interacted with PKC. Future functional analysis for the relationship between the specific type of PKC and nuclear phosphorylation might provide valuable information about the role of HMGB1 in tumor progression and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…PKC isozymes and cancer, PKC isozymes, especially PKC and , are involved in the Pgp-mediated MDR in several types of cancer, such as colon cancer [119][120][121], pancreatic cancer [399], gastric cancer [157], breast cancer [55], leukemia [513], and prostate cancer [447]. In general, inhibition of PKC isozymes that regulate P-gp leads to reduced MDR and enhanced cancer cell apoptosis.…”
Section: Pkc Isozymes and Mdrmentioning
confidence: 99%
“…PKC also regulates transforming growth factor (TGF)-1-induced expression of the matrix adhesion molecules, fibronectin and laminin, leading to the induction of E-cadherin [117,118]. In addition, PKC can induce Pgp-mediated MDR in human colon cancer cells [119][120][121]; thus, downregulation of PKC may increase the sensitivity to anticancer agents [122].…”
Section: Colonmentioning
confidence: 99%